GAMBARAN TINGKAT KECEMASAN TENAGA KESEHATAN DALAM MENANGANI PASIEN PADA SAAT PANDEMI COVID-19 - Irawati Irawati; Erwin Erwin; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
The spread of COVID-19 continues to increase, causing anxiety for health workers as the frontline in providing health services. The purpose of this study was to describe the level of anxiety of health workers in handling patients during the COVID-19 pandemic. This study used a quantitative descriptive design with 57 respondents as health workers using a total sampling technique using a questionnaire measuring instrument. The analysis used was univariate analysis. The results showed that most of the anxiety levels of health workers in handling patients during the COVID-19 pandemic were mild anxiety as many as 30 people (52.6%). Most of the respondents aged 26-35 years did not experience anxiety as many as 19 people (33.3%). Most of the female respondents experienced mild anxiety levels as many as 27 people (47.4%). Most of the respondents who were married experienced mild anxiety levels as many as 24 people (42.1%). Most of the respondents with the last education of DIII experienced mild anxiety level as many as 27 people (47.4%). Most of the respondents in the nursing profession experienced a mild level of anxiety as many as 18 people (31.6%). Health workers have an important role during the COVID-19 pandemic and are the most vulnerable to being exposed to COVID-19 so that it causes anxiety if not handled properly, mild anxiety can become anxiety with the category of severe anxiety level. This research is expected to provide information for health workers so that they are able to adapt to the COVID-19 pandemic and prevent other psychological problems. Keywords: Anxiety, the COVID-19 Pandemic, health workers